The Japanese conspiracy : the Oahu sugar strike of 1920 - Duus, Masayo, 1938-2022 (University of California Press, 1999)
A community of sugar cane workers from Japan strike for a wage increase in 1920 Oahu, straining relations between Japan and the United States, underscoring racial tensions between Japanese labor and the American sugar industry, and leading to the passage of the Japanese Exclusion Act of 1924.